The role of URO17® in diagnosis and follow up of bladder cancer patients - Mohamed Ibrahim; Joshua Rabinowitz; Rebecca Hilbert; Aruni Ghose; Samita Agarwal; Rajiv Swamy; Ismail Bulut; Mirian Guttierrez; Ebtisam Buali; Ekram Nassar; Parag Jhavar; Fatima Al-Hashimi; et al. (BMC Urology, 2024)
Abstract Objective to evaluate the role of urinary URO17® biomarker in the detection of urothelial tumors in haematuria patients and the detection of recurrence in non-muscle invasive bladder urothelial tumors. Materials and methods Our study was formed of two cohorts of patients, group I represents patients presenting with haematuria (n = 98), while group II represents patients with known non-muscle invasive bladder cancers on their scheduled follow up cystoscopic investigation (n = 51). For both groups, patients were asked to provide urine samples before cystoscopy, either primary as part of the haematuria investigation or as a scheduled follow-up. Urine samples were sent anonymously for standard urine cytology and URO17® biomarker immunostaining. Results were compared to cystoscopic findings using Chi-square analysis and Fisher’s exact test (P < 0.05). Results Group I was formed of 98 patients, with an average age of 60 years. URO17® showed 100% sensitivity and 96.15% specificity with a negative predictive value (NPV) of 100 and a positive predictive value (PPV) of 95.83. The results showed statistical significance with P value < 0.001. Group II was formed of 51 patients, with an average age of 75 years. URO17® was shown to have a sensitivity of 85.71% and NPV of 95.45. Eleven patients of group II were on scheduled BacillusCalmette-Guerin (BCG) and another 5 received Mitomycin C (MMC). The overall results of both groups combined (n = 149) showed statistical significance between flexible cystoscopy results and the results of urinary URO17® and urine cytology. Conclusion URO17® has a potential to be a reliable test for diagnosis and follow up of urothelial cancer patients and a screening tool adjunct to flexible cystoscopy. Trial Registration Not applicable as the current study is not a clinical trial, as per according to the National Institutes of Health, “studies that involve a comparison of methods and that do not evaluate the effect of the interventions on the participant do not meet the NIH clinical trial definition.”